Правова природа та особливості застосування стандартів НАТО у діяльності Національної гвардії України в умовах воєнного стану - Галай, Вікторія Олександрівна; Halai, Viktoriia (Київський інститут Національної гвардії України, 2025)
The article examines the issue of legal regulation regarding the implementation of NATO standards in the activities of the National Guard of Ukraine under martial law. Emphasis is placed on the need to adapt national legislation to international standards in order to enhance the state's defense capabilities and deepen cooperation with the Alliance. The article analyzes administrative, operational, and logistical (material-technical) NATO standards and considers key normative legal acts regulating Ukraine's cooperation with NATO in the fields of security and defense. Differences between the personnel policy and logistical support of the National Guard of Ukraine and NATO standards are identified. Solutions are proposed based on the integration into a unified training system of the security and defense sector, along with the need for the adoption of a comprehensive normative document to clearly define the capabilities of the National Guard of Ukraine in accordance with military standardization processes and interoperability with NATO structures based on specified criteria.
Legal nature and specifics of the application of NATO standards in the activities of the National Guard of Ukraine under martial law
У статті досліджено питання правового регулювання впровадження стандартів НАТО у діяльність Національної гвардії України в умовах воєнного стану. Акцентовано увагу на необхідності адаптації національного законодавства до міжнародних стандартів для підвищення обороноздатності держави та поглиблення співпраці з Альянсом. Проаналізовано адміністративні, оперативні й матеріально-технічні стандарти НАТО та розглянуто ключові нормативно-правові акти, що регламентують взаємодію України з НАТО у сфері безпеки і оборони. Виявлено відмінності між кадровою політикою та матеріально-технічним забезпеченням Національної гвардії України і стандартами НАТО. Запропоновано шляхи їх усунення на основі інтеграції до єдиної системи підготовки сектору безпеки і оборони, а також зазначено потребу у прийнятті комплексного нормативного документу для чіткого формування спроможностей Національної гвардії України відповідно до процесів військової стандартизації та сумісності зі структурами НАТО за визначеними критеріями
Keywords: правове регулювання; національна безпека; державна безпека; стандарти НАТО; Національна гвардія України; доктрина; візія; воєнний стан; legal regulation; national security; state security; NATO standards; National Guard of Ukraine; doctrine; vision; martial law